Integrated Science Learning with Connected Model Based on Ethnoscience to Enhance the Creative Thinking Dimension of Pancasila Student Profile - Avifatun, Nur; Firdaus, Firdaus (Lensa: Jurnal Kependidikan Fisika, 2024)
This study aims to analyze the effectiveness of integrated science learning using a connected model based on ethnoscience to improve the Pancasila Student Profile, particularly in the creative thinking dimension. A quantitative approach with a quasi-experimental method was employed. The research sample consisted of 30 eighth-grade students from MTs Ma'arif Garung, divided into experimental and control groups. Research instruments included pretests, posttests, observation sheets, and interviews. Data analysis was conducted using t-tests and N-Gain analysis with SPSS software. Results indicated that the average N-Gain score for the experimental class reached 60%, categorized as effective, while the control class scored 42.3%. The t-test yielded a significance value of 0.000 (<0.05) and a t-value of 3.846 (>t-table 2.074), indicating that the ethnoscience-based connected learning model effectively enhanced students' creative thinking skills.